Embedding Hindsight Reasoning in Separation Logic - Meyer, Roland; Wies, Thomas; Wolff, Sebastian (Proceedings of ACM on programming languages, 2023)
Automatically proving linearizability of concurrent data structures remains a key challenge for verification. We present temporal interpolation as a new proof principle to guide automated proof search using hindsight arguments within concurrent separation logic. Temporal interpolation offers an easy-to-automate alternative to prophecy variables and has the advantage of structuring proofs into easy-to-discharge hypotheses. Additionally, we advance hindsight theory by integrating it into a program logic, bringing formal rigor and complementary proof machinery. We substantiate the usefulness of temporal interpolation by implementing it in a tool and using it to automatically verify the Logical Ordering tree. The proof is challenging due to future-dependent linearization points and complex structure overlays. It is the first formal proof of this data structure. Interestingly, our formalization revealed an unknown bug and an existing informal proof as erroneous.